1979
DOI: 10.2134/agronj1979.00021962007100020036x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of 15N‐Labeled Nitrate by Sugar Beets from Depths Greater than 180 CM1

Abstract: Previous investigations had shown that irrigated sugar beets (Beta vulgaris L.) extracted NO3− from depths of 135 cm. Since excessive N availability late in the growing season can adversely affect root sucrose content, it was necessary to determine if the plant could extract NO3− from even greater depths. Thus, a field experiment was conducted on a Typic Haplustoll with 15N labeled NO‐N placed at depths of 180, 210, and 240 and below the soil surface in tracer amounts. Petiole 15N uptake was monitored on 2 Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…A classical study from Nebraska, USA showed roots of white cabbage extending to 2.4 m and numerous other vegetables having root depths in the range of 1-2 m (Weaver and Bruner, 1927). Other studies from Nebraska have shown 15 N uptake from 1.8 m by corn and from 2.4 m by sugar beet over a growing season (Gass et al, 1971;Peterson et al, 1979). Recently we found uptake of significant amounts of 15 NO − 3 by roots growing down to 2.5 m depth of the catch crop fodder radish (Kristensen and Thorup-Kristensen, 2004).…”
Section: Introductionmentioning
confidence: 60%
“…A classical study from Nebraska, USA showed roots of white cabbage extending to 2.4 m and numerous other vegetables having root depths in the range of 1-2 m (Weaver and Bruner, 1927). Other studies from Nebraska have shown 15 N uptake from 1.8 m by corn and from 2.4 m by sugar beet over a growing season (Gass et al, 1971;Peterson et al, 1979). Recently we found uptake of significant amounts of 15 NO − 3 by roots growing down to 2.5 m depth of the catch crop fodder radish (Kristensen and Thorup-Kristensen, 2004).…”
Section: Introductionmentioning
confidence: 60%
“…While the present experiment adds to the few studies showing significant N uptake from below 1 m in the soil (Gass et al 1971;Daigger and Sander 1976;Peterson et al 1979;Kristensen and Thorup-Kristensen 2004a), we do not know how important this is in agriculture in general. How many crop species can grow this deep, how many soils will allow this, and how much N can be taken up from the deep soil layers in ordinary agricultural practice?…”
Section: Root Growth and Soil N Depletionmentioning
confidence: 78%
“…Still, there is increasing evidence of large differences in rooting depth among crop species (Kristensen and Thorup-Kristensen 2004a;Smit and Groenwold 2005) and evidence that several important crops may have significant rooting to well below 1.0 m (Daigger and Sander 1976;Peterson et al 1979;Barraclough 1989;Addiscott and Darby 1991;Stone et al 2002). Significant N uptake from soil layers between 1.0 and 3.0 m have also been shown (Gass et al 1971;Daigger and Sander 1976;Peterson et al 1979;Kristensen and Thorup-Kristensen 2004a). The need to consider differences in crop rooting depths when simulating soil N dynamics was stressed by Delgado et al (2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that deep-rooted crops can mitigate N leaching losses by capturing N from deep soil or subsoil horizons (Peterson et al 1979;Huang et al 1996;Thorup-Kristensen 2001;Kristensen and Thorup-Kristensen 2004). Bahiagrass, Paspalum notatum Flüggé, may be a good candidate for mitigating excess soil N since it has been reported to have a large and a deep fibrous root system (Burton 1943).…”
mentioning
confidence: 99%